2011
DOI: 10.1155/2011/531403
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Its Relationship with Occupational Injury in the Canadian Workforce

Abstract: Objectives. To examine associations between obesity and occupational injury. Methods. Participants consisted of a representative sample of 7,678 adult Canadian workers. Participants were placed into normal weight, overweight, and obese categories based on their body mass index. Different injury types, location, and external causes were measured. Logistic regression was used to estimate relationships. Results. By comparison to normal weight workers, obese workers were more likely to report any occupational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 18 publications
(22 reference statements)
4
30
1
1
Order By: Relevance
“…Although shorter sleep durations or higher BMI have been generally associated with increased work-related injury risk (Chau et al, 2004;Janssen et al, 2011;Kling et al, 2010;Lombardi et al, 2010;Pollack & Cheskin, 2007;Schulte et al, 2008), this is the first large US population-based study that has examined these two risk factors simultaneously to determine if they affect injury risk independently (e.g., additive effect) or if BMI modifies the effects of short sleep (or vice versa) on injury risk (e.g., interactive effect). Although we found no statistically significant interactive effect among sleep duration and BMI, their individual associations with injury risk are generally consistent with the findings of previously published studies that examined these factors separately (Chau et al, 2004;Connor et al, 2001;Dembe et al, 2005;Folkard et al, 2005;Janssen et al, 2011;Lombardi et al, 2010;Melamed & Oksenberg, 2002;Pollack & Cheskin, 2007;Schulte et al, 2008;Teran-Santos et al, 1999;Virtanen et al, 2009;Williamson et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Although shorter sleep durations or higher BMI have been generally associated with increased work-related injury risk (Chau et al, 2004;Janssen et al, 2011;Kling et al, 2010;Lombardi et al, 2010;Pollack & Cheskin, 2007;Schulte et al, 2008), this is the first large US population-based study that has examined these two risk factors simultaneously to determine if they affect injury risk independently (e.g., additive effect) or if BMI modifies the effects of short sleep (or vice versa) on injury risk (e.g., interactive effect). Although we found no statistically significant interactive effect among sleep duration and BMI, their individual associations with injury risk are generally consistent with the findings of previously published studies that examined these factors separately (Chau et al, 2004;Connor et al, 2001;Dembe et al, 2005;Folkard et al, 2005;Janssen et al, 2011;Lombardi et al, 2010;Melamed & Oksenberg, 2002;Pollack & Cheskin, 2007;Schulte et al, 2008;Teran-Santos et al, 1999;Virtanen et al, 2009;Williamson et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, Schmier et al (2006) demonstrated that overweight or obese employees had not only a higher injury risk, but also higher sick leave or disability use, and health care costs, based on claims data analyses. In a population study of Canadian workers, obese workers were found to have injury risks that were 40-49% higher than normal-weight workers (Janssen et al, 2011), and the effect was strongest among sedentary workers, women, and those ≥40 yrs of age. However, a review by Pollack and Cheskin (2007) points out the need to further examine the association between obesity and traumatic injury risk using studies with sufficient sample size that control for confounding variables.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Obese workers are often less productive at work 2) , and have increased absenteeism 3) , occupational injuries 4) , morbidity and use of health services 5) . In recent decades, the prevalence of obesity has been increasing worldwide 6) .…”
mentioning
confidence: 99%
“…General and postpartum stress as causes of obesity: Physical and mental stress have been implicated as potential causes of obesity [156,157]. Job strain and job related stress have also been implicated in the causes of obesity and overweight [158,159]. Postpartum stress is also implicated as causes of maternal weight retention and obesity [157].…”
Section: N Lower Basal Metabolic Rate (Bmr) As a Cause Of Obesitymentioning
confidence: 99%